Profitabilitas dan Transparansi dalam Meningkatkan Nilai Perusahaan - Laksmi P, Kadek Wulandari; Ariwangsa, I G.N. Oka; Niron, Vernanda Christine (Sekolah Tinggi Ilmu Ekonomi Bank BPD Jateng, 2024)
This research aims to explore the impact of profitability and transparency on firm value. Sampleselection was conducted selectively using the purposive sampling method, resulting in a total of 66samples. The study was carried out on manufacturing companies in the food and beverage sub-sectorlisted on the Indonesia Stock Exchange during the period 2020-2022. The choice of the food sub-sectoras the research focus was based on its performance improvement during the specified period, despitefacing challenges from the COVID-19 pandemic in 2020. Investors also demonstrated increasedinterest in this sub-sector. The applied method of data analysis was multiple linear regression. Theresearch findings indicate that both profitability and transparency have a significantly positive impacton firm value. These results offer a deeper understanding of the positive relationship betweenprofitability, transparency, and the assessment of firm value in the context of food and beveragemanufacturing companies during the research period